Research on Nonlinear Dynamics Modeling and Simulation of Harmonic Gear Drive - Yang Luo; Manyi Chen; Jie Zhang; Ran Yang; Han Zhang (Jixie chuandong)
Due to the particularity of the structure，the hysteretic stiffness and dynamic friction belong to the inherent properties of harmonic gear drive. Traditional models consider the stiffness as a fixed stiffness or segmented stiffness model，and the friction as a static friction model. Such simplification will lead to the decrease of the dynamic analysis accuracy of harmonic gear drive system. In order to improve the dynamic analysis accuracy and transmission performance of harmonic gear drive，considering the nonlinear hysteretic stiffness and dynamic friction phenomenon，a dynamics model of harmonic gear drive based on memory characteristic hysteresis stiffness and LuGre dynamic friction is proposed，and the corresponding simulation model is established. The effects of harmonic gear parameters on the system output are discussed. The results show that the stiffness hysteresis phenomenon leads to the decrease of system output and transmission efficiency， the larger the transmission stiffness coefficient， the more stable the system， the larger the damping torque coefficient， the lower the transmission efficiency.